Genomic and Functional Characteristics of Human Cytomegalovirus Revealed by Next-Generation Sequencing - Sijmons, Steven (MDPI, 2014)
The complete genome of human cytomegalovirus (HCMV) was elucidated almost 25 years ago using a traditional cloning and Sanger sequencing approach. Analysis of the genetic content of additional laboratory and clinical isolates has lead to a better, albeit still incomplete, definition of the coding potential and diversity of wild-type HCMV strains. The introduction of a new generation of massively parallel sequencing technologies, collectively called next-generation sequencing, has profoundly increased the throughput and resolution of the genomics field. These increased possibilities are already leading to a better understanding of the circulating diversity of HCMV clinical isolates. The higher resolution of next-generation sequencing provides new opportunities in the study of intrahost viral population structures. Furthermore, deep sequencing enables novel diagnostic applications for sensitive drug resistance mutation detection. RNA-seq applications have changed the picture of the HCMV transcriptome, which resulted in proof of a vast amount of splicing events and alternative transcripts. This review discusses the application of next-generation sequencing technologies, which has provided a clearer picture of the intricate nature of the HCMV genome. The continuing development and application of novel sequencing technologies will further augment our understanding of this ubiquitous, but elusive, herpesvirus.